MODERNISASI PENDIDIKAN ISLAM (TELAAH PEMIKIRAN FAZLUR RAHMAN) - Moch Tohet (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
As a thinker was born in the early 20th century AD, Fazlur Rahman had lived at a time when science and technology had developed. According to him, the development of science and technology is felt to bring currents and impacts on education, especially Islamic education. In Fazlur Rahman's view, what must be done to renew Islamic education is to bring Islamic education to the right vision and mission, namely education that has the vision and mission of the Qur'an. Where the main vision and mission of the Qur'an is to "repair the damage on this earth and improve its condition", to "call for a good condition and forbid a bad condition", and to build a social order on a solid ethical foundation. According to him, basically all the problems of "modernization" of Islamic education must be able to make it increase the creative intellectual productivity of Islam in all fields. Modernization of Islamic education is not only about physical equipment and teaching equipment such as books, but more than that modernization must be sought more on building Islamic intellectualism itself